Sampling for Integrated Auditing Objectives. - Hansen, Don R.; Shaftel, Timothy L. (The Accounting Review, 1977)
Abstract Integrated sampling procedures have been suggested in recent accounting literature. Yuji Ijiri and Robert Kaplan have proposed a nonlinear model which, when solved, yields a sampling procedure which satisfies several auditing goals. This paper presents a solution procedure for the proposed model. The solution procedure takes advantage of lagrange multipliers to create a problem which is linear in the constraints and convex in the objective function. A search technique then is used in conjunction with the convex simplex method to solve the problem. The procedure is used to test the model results in an actual auditing environment. The results of this study indicate the feasibility of using this approach for generating sampling designs.